(untitled) (Jurnal Teknologi (Sciences & Engineering), 2013)
Electrical capacitance tomography (ECT) is one of the systems used to inspect closed pipe flow. This paper will present the proposed segmented excitation of electrodes with a focus on the low resolution problem.Â Modelling of 8, 12 and 16 electrodes is done using COMSOL Multiphysics. The number of excitation electrodes is increased until half of the electrodes are excited at the same time. The electrical potential distribution is analyzed and the voltage value at the centre of the pipe is captured. The results show that there is improvement of electrical potential and voltage value in proportion to the number of electrodes excited at the same.